PHYSICAL ACTIVITY FOR BETTER HEALTH – SUMMARY OF GUIDELINES AND RECOMMENDATIONS - Jasmina Pluncevic Gligoroska; Sanja Mancevska; Sunchica Petrovska; Beti Dejanova (Ss. Cyril and Methodius University, Faculty of Physical Education, Sport, and Health, 2018)
Physical activity is the fundamental human ability and basis for surviving at all. It can be described by performance parameters: frequency, duration and intensity. Physical activity is key determinant for maintaining of good conditions for vital physiological systems, such as cardiovascular, locomotors, respiratory, nervous etc. The main goal of developing the strategy for physical activity for better health is to control of noncomunicable diseases. The most important world health organizations (including World Health Organization, World Health Assembly etc) are united with the global targets to reduce the prevalence of insufficient physical activity and consecutively increase the level of physical activity. There are many different forms, kinds and levels of intensity of physical activity. The proper prescribing of the physical activity should lead to attaining the very important targets: reduction of premature mortality from cardiovascular diseases, cancer, diabetes, high blood pressure and obesity. To fulfill the proposed health benefits physical activity should be dosed according to individual features and needs. The World Health Organization and range of other international and national health organizations made a set of recommendations for different populations group which could help to practice physical activity safely and with optimal results.
Keywords: physical activity; recommendations